The Influence of Self Efficiency and Internal Locus of Control on Career Planning of Students Departement of Beauty and Cosmetology Padang State University - Yanita, Merita; Giatman; Syah, Nurhasan (The Indonesian Journal of Computer Science, 2023)
Career planning is a process of determining activities or plans to be carried out in the future as a step towards achieving predetermined goals including knowledge and understanding of oneself, knowledge and understanding of work, and the use of correct reasoning between oneself and the world of work. . Individual career planning is influenced by several factors, including self-efficacy and internal locus of control. The purpose of this study was to determine whether there is an influence between self-efficacy and internal locus of control on the career planning of students of the Department of Beauty and Cosmetology, Padang State University. This research uses ex post-facto method. The population in this study were 459 students of the Department of Beauty and Cosmetology, Padang State University. From a total population of 459 students, a sample of 210 students was taken. The research sample was taken 210 students taken randomly. The data collection instrument used a scale, while data analysis used multiple regression techniques. Based on the analysis of research data, the results obtained 1) there is a significant influence of self-efficacy on career planning of students of the Department of Beauty and Cosmetology, Padang State University, 2) there is a significant influence of internal locus of control on career planning of students of the Department of Beauty and Cosmetology, Padang State University, 3) there is a simultaneous effect of self-efficacy and internal locus of control on the career planning of students of the Department of Beauty and Cosmetology, Padang State University.